TRENDS OF WOMEN'S CANDIDACY IN NATIONAL ELECTIONS OF NEPAL - Shrestha, Amrit Kumar (Researcher: A Research Journal of Culture and Society, 2018)
The study area of this article is women's candidacy in national elections of Nepal. It focuses on five national elections held from 1991 to 2013. It is based on secondary source of data. The Election Commission of Nepal publishes a report after every election. Data are extracted from the reports published by the Election Commission and analyzed with the help of the software SPSS. This article analyzes only facts regarding the first-past-the-post (FPTP) electoral system. Such a study is important in order to lead to new affirmative action policies that will enhance gender mainstreaming and effective participation in all leadership and development processes. The findings will also be resourceful to scholars who are working in this field. The findings from this investigation provide evidence that the number of women candidates in national elections seems almost invisible in an overwhelming crowd of men candidates. The number of elected women candidates is very few. Similarly, distribution of women candidates is unequal in geographical regions. Where the human development rate is high the number of women candidates is greater. The roles of political parties of Nepal are not profoundly positive to increase women's candidacy. Likewise, electoral systems are responsible to influence women‟s chances of being elected. FPTP electoral system is not more favorable for women candidates. This article recommends that if a constituency would reserve only for women among three through FPTP then the chances of 33 percent to win the elections by women would be secured. Researcher: A Research Journal of Culture and Society Vol. 3, No. 3, January 2018, Page: 47-62